PERLINDUNGAN KONSUMEN TERHADAP PEMASANGAN IKLAN SHORT MESSAGE SERVICE PADA PERUSAHAAN TELEKOMUNIKASI TELKOMSEL DI KOTA MAKASSAR - Juwenie Mangiri (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2020)
The development of information technology now has a significant impact on the development of business transactions in the trading system. One of the application of information technology is in the delivery of advertisements to potential consumers of goods and services through the media Short Message Service (SMS). The usage of SMS media is certainly very beneficial for telecommunications companies and business operators. However, not all the consumers of telecommunications companies feel comfortable with the short message containing the advertisement. In hence, this article analyzes consumer protection against advertising through SMS media at PT Telkomel in Makassar City. This article will also look at the advantages and disadvantages for consumers as a result of advertising through SMS media. The purpose of writing to determine the legal protection of consumers and the advantages and disadvantages for consumers against advertising on PT Telkomsel via SMS in the city of Makassar. The result of the study indicate that consumer protection protects consumers from the actions of business actors who in adversiting their products throught SMS have violated consumer rights which are cleary regulated concerning Consumer Protection, and know that the existens of advertisements through SMS in more harmful consumers especially in terms of consumer privacy.